The Impact of Recruitment and Selection on Human Resource Quality in the Digital Era - Albashori, Muhammad Fatkhurohman; Nugroho, Himawan Agung; Wahyuning, Sri; Mubarok, Ade; Faturochman, Ersha (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
In today's rapidly evolving digital era, organizational success is largely determined by the ability to manage quality human resources (HR). Competent, adaptive, and innovative HR are key for companies to survive and compete amidst the dynamic business environment. One important factor in creating quality HR is an effective and targeted recruitment and selection process. This study uses a quantitative approach. The population in this study is all employees or staff at companies/agencies that have implemented a digital-based recruitment and selection system. Data analysis was conducted using Multiple Linear Regression with SPSS. Based on the results of the study and analysis, it can be concluded that recruitment and selection have a significant influence on the quality of human resources in the digital era. A recruitment and selection process that is designed effectively, systematically, and technology-based can produce a competent, adaptive workforce with abilities in accordance with the demands of the development of the modern workplace.